Fabrication and Characterization of Timolol Maleate and Brinzolamide Loaded Nanostructured Lipid Carrier System for Ocular Drug Delivery - Shrivastava, Nupur; Khan, Saba; Baboota, Sanjula; Ali, Javed (Current Drug Delivery, 2018)
Background: The combination of timolol maleate (TM) and brinzolamide (BRZ) has potential therapeutic prospects for treating glaucoma. However, the conventional formulation of TM and BRZ exhibits sub optimal therapeutic effects attributable to the poor ocular bioavailability of these drugs. Objective: Therefore, the aim of the present study was to design and evaluate TM and BRZ loaded nanostructured lipid carrier (NLC) to enhance the bioavailabilities, permeation and precorneal residence time of these drugs that would result in efficacious treatment of glaucoma. Methods: In this study, combination of drugs with different characteristic properties was loaded in NLC. The dual drugs loaded NLC was prepared by melt emulsification technique and evaluated for characteristic properties such as particle size (PS), polydispersity index (PDI), entrapment efficiency (EE) and drug loading (DL), in vitro drug release and ex vivo drug penetration studies. Results: The PS and PDI of optimized NLC formulation were found to be 110.36 ±0.47 nm and 0.24 ± 0.00 respectively. The EE and DL of optimized NLC formulation were found to be 77.12 ± 0.64 % and 0.360 ± 0.01 % for TM respectively; whereas, 70.73±0.64 % and 0.71 ± 0.02 %for BRZ respectively. In vitro drug release studies showed a comparable initial rapid release of around 34 ± 2.90 % for TM and 38 ± 3.10 % for BRZ in the first 5 h followed by sustained drug release around 72.29 ± 5.90 % for TM and 70.08 ± 6.40 % for BRZ until last 24 h. Ex vivo drug penetration studies showed about 33.47 ± 2.80 % of TM and 36.20 ± 2.80 % of BRZ permeated in the first 5 h followed by 72.30 ± 6.40% of TM and 67.69 ± 6.500 % of BRZ until 24 h. There was remarkable enhancement in the release pattern and permeation of both the drugs from NLC as compared to that from their suspension. Conclusion: With dextrous optimization of dose and excipients concentration, the dual drugs with different characteristic properties can be successfully loaded in NLC formulation.
Keywords: Timolol maleate